Feed Supplementation with Red Seaweeds, Chondrus crispus and Sarcodiotheca gaudichaudii, Reduce Salmonella Enteritidis in Laying Hens - Kulshreshtha, Garima; Rathgeber, Bruce; MacIsaac, Janice; Boulianne, Martine; Brigitte, Lehoux; Stratton, Glenn; Thomas, Nikhil A.; Critchley, Alan T.; Hafting, Jeff; Prithiviraj, Balakrishnan (Frontiers in Microbiology, 2017)
Salmonella Enteritidis (SE) is vertically transmitted to eggs from laying hens through infected ovaries and oviducts. S. Enteritidis can also penetrate the eggshell from contaminated feces. Reducing S. Enteritidis in laying hens is vital to provide safer eggs and minimize the spread of salmonellosis to humans. Antibiotics have been widely used to control bacterial diseases in broilers and laying hens. However, there is a major concern that the use of antibiotics leads to the development of antibiotic resistance and adverse effects on microbiota of the treated birds. Thus, there is an interest in developing alternatives to antibiotics, such as dietary prebiotics. In the present study, feed supplemented with the red seaweeds: Chondrus crispus (CC) or Sarcodiotheca gaudichaudii (SG), was offered to laying hens late in production to control S. Enteritidis. Diets contained one of the following; 2% or 4% Chondrus crispus (CC2, and CC4, respectively) or Sarcodiotheca gaudichaudii (SG2 and SG4, respectively). Chlortetracycline was used in the positive control diet. During week-4, 48 birds were orally challenged with 2 ×109 CFU/mL of S. Enteritidis. Eggs and fecal samples were collected 1, 3, 5 and 7 days’ post inoculation. Birds were euthanized and organs (ceca, ovary, liver and spleen) were sampled and analyzed for the presence of S. Enteritidis, 7 days’ post inoculation. Results showed that seaweed reduced the negative effect on body weight and egg production in S. Enteritidis-challenged laying hens. Analysis of fecal samples showed that the antibiotic (CTC) reduced S. Enteritidis in the intestinal tract and fecal samples, 3 days’ post inoculation. Fecal samples from Chlortetracycline and CC4 supplemented birds tested negative for S. Enteritidis on day 5 and 7 post inoculation (lowest detection limit =10-1). S. Enteritidis colonization in the ceca was also significantly reduced in birds fed CC (4%) and Chlortetracycline. Blood serum profiles revealed that there were no significant differences in serum aspartate transaminase (AST) and sodium. However, the level of serum immunoglobulin (IgA) was higher in the CC4 treatment. The relative abundance of Lactobacillus acidophilus was significantly higher in CC4 while, the abundance of the pathogenic bacteria, Clostridium perfringens and Salmonella Enteritidis were reduced